2019
DOI: 10.4103/ijpvm.ijpvm_227_18
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Vitamin D supplementation in physical performance of Iranian elite athletes

Abstract: Background: There has been no report of the vitamin D status of the professional athletes from Iran to date. This study was performed to evaluate the efficacy of weekly vitamin D supplementation on athletic performance in Iranian athletes expedited to Asian competition in Taipei, China, 2015. Methods: This study was a randomized controlled clinical trial. Seventy subjects were enrolled in the study. The athletes were randomly divided into two groups: vitamin D supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Previous literature suggests vitamin D may increase performance, specifically muscular strength, due to an increase in the size and number of type II muscle fibers. 46 A study by Alimoradi et al 47 showed significant increases in leg press and sprint tests in athletes supplemented with 50,000 IU wk −1 vitamin D. Therefore, the NMFS should focus on increasing the amount of vitamin D rich food items for WLFFs to meet their vitamin D nutrient needs as well as consider providing a more significant amount of nutrient-dense food options to increase the food quality provided to WLFFs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature suggests vitamin D may increase performance, specifically muscular strength, due to an increase in the size and number of type II muscle fibers. 46 A study by Alimoradi et al 47 showed significant increases in leg press and sprint tests in athletes supplemented with 50,000 IU wk −1 vitamin D. Therefore, the NMFS should focus on increasing the amount of vitamin D rich food items for WLFFs to meet their vitamin D nutrient needs as well as consider providing a more significant amount of nutrient-dense food options to increase the food quality provided to WLFFs.…”
Section: Discussionmentioning
confidence: 99%
“…We found association between serum 25(OH)D levels and results in the S20M, 20Y, and RSI, with better results in fitness tests among those players who had higher levels of 25(OH)D Meanwhile, the findings of previous studies that investigated the effects of 25(OH)D levels on sports performance are not consistent. Koundourakis et al, (2014) found a correlation of sprint and jumping test results with 25(OH)D levels in professional Greek soccer players, whereas several other studies did not [ 20 , 25 ]. Additionally, some studies concluded that soccer players with lower 25(OH)D levels have lower results in performance tests [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…A significant correlation was found between vitamin D levels and muscle functioning assessed with jumping, sprinting, leg press, and aerobic capacity tests in professional Greek soccer players [ 9 ]. Alimoradi et al, (2019) also recorded a positive correlation between higher vitamin D concentration and improvements in sprint and leg press tests in a group of Iranian soccer players supplemented with vitamin D in comparison with players who were not supplemented [ 20 ]. Conversely, Ksiazek et al, (2016) did not find an association between vitamin D levels and lower limb muscle strength in professional soccer players [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The subject group received 50,000 IU vitamin D weekly and the control group did not receive any vitamin D supplementation. After the study of 8 weeks, they stated as the result of the study that weekly vitamin D supplementation caused an increase in calcifediol in the blood circulation and this increase improve the strength and speed performance of the subject group (Alimoradi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%